Mezcal vinasses treatment: A review of assessed processes - Díaz-Barajas, Sergio; Moreno-Andrade, Iván; Garzón-Zúñiga, Marco A. (Tecnología y ciencias del agua, 2024)
Mezcal is an alcoholic beverage made in Mexico. This industry produces mezcal vinasses, which are complex wastewater with a high concentration of organic matter (35 000 to 122 860 mg COD/l), low pH (3.60-3.94) and recalcitrant compounds such as phenols (478-1 460 mg gallic acid/l) and sulfates (308-947 mg/l), its disposal without treatment to the environment poses a danger to soil and water bodies. The present study seeks to present and discuss the current technological development in the treatment of mezcal vinasses and to identify the systems with the most significant potential for its application. The mezcal vinasses treatments with the best COD removal efficiencies are fungal and anaerobic (80 %). Ozonation has potential as a pretreatment, which can remove more than 80 % of phenols. Some hybrid systems can remove > 90 % COD. However, these treatments do not include the concept of "circular economy", so its implementation is seen as an expense that sometimes cannot be afforded by producers. One option includes the revalorization for generating an economic benefit to producers. Biorefinery treatment, in which various types of energy have been obtained, such as biohydrogen, methane, and bioelectricity by applying different bioprocesses sequentially, was identified as the treatment with the best potential.